2013
DOI: 10.2478/pjvs-2013-0043
|View full text |Cite
|
Sign up to set email alerts
|

The effects of experimental administration of low doses of zearalenone on the histology of ovaries in pre-pubertal bitches

Abstract: The experiment involved 30 clinically healthy Beagle bitches aged approximately 70 days with an initial body weight of approximately 8 kg. The animals were randomly divided into two experimental groups (EI and EII) and a control group of 10 animals each. Group EI was administered 50 μg of body weight zearalenone/kg per os for 42 days, group EII received 75 μg of body weight zearalenone/kg per os for 42 days, and the control group was administered placebo per os for 42 days. The bitches were ovariectomized at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Although few data on mycotoxin toxicity in dogs are available, 19,20,51,52 it is possible to estimate the exposure degree and calculate the ADI and SPDL for mycotoxins ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although few data on mycotoxin toxicity in dogs are available, 19,20,51,52 it is possible to estimate the exposure degree and calculate the ADI and SPDL for mycotoxins ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of ZEA in most animals are similar to those arising from exposure to high concentrations of estrogen, characterized by infertility, abnormal lactation, stillbirth, abortion, mastitis, vaginitis or vaginal and rectal prolapse . Gajecka et al reported alterations in the dog reproductive system after 7 days at daily doses of 200 µg kg −1 body weight (BW) and effects on the blood concentrations of sexual hormones following exposure to smaller doses for a longer period of time (75 µg kg −1 BW for 42 days) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was consistent with the increase in plasma β‐ZEL reported in another paper (Gajęcka et al., ). Immunohistochemical investigations performed on ovarian specimens collected at the end of ZEN administration revealed no positive staining for ERα in all experimental animals; a dose‐related decline in ERβ‐related immunostaining was instead observed in oocyte nuclei, granulosa cells and interstitial cells from both treated groups when compared to control animals (Gajęcka, ). Finally, a further report (Stopa et al., ) addressed the morphometric and histologic changes in bitches exposed as described above (0, 50 or 75 μg ZEN/kg bw for 42 days).…”
Section: Assessmentmentioning
confidence: 97%
“…Dog and cat food has also been found to contain BPA (Kang and Kondo 2002) as well as mycotoxins (Leung et al 2006). Experimental studies showed that zearalenone (ZEA) affects the reproductive organs of bitches (Gajęcka 2013), but very few studies have examined adverse effects of BPA or other plasticizers (such as phthalates) in dogs. Dog toys have been found to contain both BPA and phthalates and, therefore, could represent another route of exposure (Wooten and Smith 2013; Nohrborg 2015).…”
Section: Endocrine Disruptors and Dogs And Catsmentioning
confidence: 99%